2004
DOI: 10.1073/pnas.0401516101
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of carbohydrate response element-binding protein (ChREBP) reduces lipogenesis as well as glycolysis

Abstract: The liver provides for long-term energy needs of the body by converting excess carbohydrate into fat for storage. Insulin is one factor that promotes hepatic lipogenesis, but there is increasing evidence that glucose also contributes to the coordinated regulation of carbohydrate and fat metabolism in liver by mechanisms that are independent of insulin. In this study, we show that the transcription factor, carbohydrate response element-binding protein (ChREBP), is required both for basal and carbohydrate-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
701
9
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(763 citation statements)
references
References 18 publications
40
701
9
13
Order By: Relevance
“…Recently, mice deleted for the ChREBP gene have been generated (23). These mice are viable but display a complex pattern of metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mice deleted for the ChREBP gene have been generated (23). These mice are viable but display a complex pattern of metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Third, ChREBP shuttles between the cytoplasm and nucleus in a glucose-responsive manner in hepatocytes (31). Fourth, mice in which the ChREBP gene has been disrupted or hepatocytes treated with siRNA to reduce ChREBP expression do not induce lipogenic gene expression in response to carbohydrate feeding or glucose, respectively (23,43). Fifth, hepatocytes prepared from ChREBP knock-out mice do not support a glucose response when transfected with a ChoRE-containing promoter, but this response can be restored by the addition of a ChREBP expression vector (44).…”
Section: Discussionmentioning
confidence: 99%
“…Although both of these processes are controlled by insulin, the intermediary regulatory mechanisms appear to be separate. The conversion of carbohydrates to fatty acids is orchestrated by the transcription factors sterol regulatory element binding protein 1 (SREBP1c) and carbohydrate response element binding protein (ChREBP), which promote the transcription of enzymes required for de novo lipogenesis in response to insulin (21,25). Genetic disruption of the SREBP pathway markedly reduces fatty acid synthesis in liver (26), but does not prevent up-regulation of ANGPTL8 with refeeding (14).…”
Section: Discussionmentioning
confidence: 99%
“…So far ChREBP has mainly been found to act as a glucose-stimulated transcriptional activator of glycolytic and lipogenic genes in hepatocytes (17)(18)(19)(20)(21) and in pancreatic ␤-cells (22,23). Recently, however, it was reported that ChREBP acts as a negative regulator of the ARNT/HIF-1␣ gene (56).…”
Section: Discussionmentioning
confidence: 99%